Automatic cardiac motion tracking using both untagged and 3D tagged MR images - Wang,H; Shi,W; Zhuang,X; Duckett,S; Tung,K; Edwards,P; Razavi,R; Ourselin,S; Rueckert,D (2012)
We present a fully automatic framework for cardiac motion tracking based on non-rigid image registration for the analysis of myocardial motion using both untagged and 3D tagged MR images. We detect and track anatomical landmarks in the heart and combine this with intensity-based motion tracking to allow accurately model cardiac motion while significantly reduce the computational complexity. A collaborative similarity measure simultaneously computed in three LA views is employed to register a sequence of images taken during the cardiac cycle to a reference image taken at end-diastole. We then integrate a valve plane tracker into the framework which uses short-axis and long-axis untagged MR images as well as 3D tagged images to estimate a fully four-dimensional motion field of the left ventricle. © 2012 Springer-Verlag.